Kajian Keberkesanan Kursus Microsot Office Excel di Politeknik Merlimau - Siti Zaleha Che Harun; Salhana Binti Sahidin Sallehudin; Roshila Samsudin (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Microsoft Office Excel is one of the software for Computer Application. Computer Application is a course that exposes participants to the skills of using Microsoft Office Word, Excel, PowerPoint, and Outlook software. Microsoft Office Specialist (MOS) is an internationally recognized professional certification. This study was conducted to measure the effectiveness of the Microsoft Office Specialist (MOS) Excel Course for 30 participants consisting of lecturers from Politeknik Merlimau. The course was conducted for 5 days for lecturers from the Department of Mechanical Engineering, Department of Electrical Engineering, Department of Civil Engineering, and Department of Mathematics and Science at Politeknik Merlimau. Data based on questionnaires given to all participants showed an increase in understanding before and after the course. This quantitative study was conducted by comparing data before and after the course. The program's achievement is evaluated based on the results of the MOS Examination, which uses a practical project-based assessment method with a 50-minute answering time. The results of the data comparison show that 8% of lecturers scored full marks, i.e., 1000, 60% of lecturers scored above 950, and 13% of lecturers scored below 950. Candidates who have passed the MOS examination will receive a professional certificate from Microsoft Corporation. The professional certificate is important for the competence of lecturers and also helps in improving the talent empowerment Key Performance Indicator (KPI) for the polytechnic. This study is expected to be evidence of Continuous Quality Improvement (CQI) in helping to improve participant achievement and continuous programs for the Microsoft Office Specialist Excel Course.